Neoindustrialization of Former Industrial Regions of Russia: The Example of “Titanium Valley" - Burnasov, Alexander; Ilyushkina, Maria; Kovalev, Yuri; Stepanov, Anatoly (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2013)
Russian economy in the 20th century experienced complex transformational processes. Havingintroduced the principles of a market economy, Russia has found itself under pressures of globalizationand neoindustrialization, which have had an effect on the nation’s industrial structure. Globalization hasexpanded state borders and opened the gates for Russian entrepreneurs to conquer world markets in oiland gas, ferrous and non-ferrous metals, engineering and chemical industries. The Urals region of Russiais developing in a very intensive way. The production cluster known as “Titanium Valley” was formedhere. This article throws light on some of the special features of its activity.